ON-BOARD FUNCTIONAL TEST AND DEBUG PLATFORM FOR PROCESSORS - ALI, GHAZANFAR (2014)
In the processor manufacturing industry, the current methodology adopted to test and debug processors is by configuring them in the test mode with the use of on-chip or off-chip testers. The tester applies a series of test stimuli and compares the responses from the processor with the predetermined responses to test or debug the processor. Due to the sequential and unconditional nature of the application of the series of these pre-determined test stimuli, the tester cannot be used for functional tests during the diagnosis. Hence, some faults that crop up only at-speed in the functional mode may not manifest during the diagnosis which is a critical problem in today's nano-scale manufacturing industry. To solve this issue, a test platform to carry out on-chip at-speed test and debug for embedded processor cores without using expensive external automatic test equipment (ATE) is proposed in this thesis. The proposed on-chip platform has the capability to test and debug the circuit under test (CUT) in both functional and test mode of operation.